"Multiple sclerosis plus": Does it influence the disease course?. Issue 2 (25th January 2020) - de Seabra, Mafalda Maria Laracho; Abreu, Pedro Miguel Paredes; Soares Mendonça, Maria Teresa; Reis, Joaquim Jorge Correia Silva; Sá, Maria José Pontes Marques; Guimarães Ferreira Almeida, Joana Cruz
Abstract: Objectives: To study the association between multiple sclerosis (MS) and other autoimmune diseases (AID). Methods: From a cohort of 635 patients with MS, 66 patients with an history of AID were selected. Controls, matched 1:1, were chosen from the population of patients with MS without autoimmune comorbidities. Further analysis aimed to compare these groups. Results: The prevalence of comorbid AID in our population was 10.4%. The mean age was 43 ± 13 years; 77% were women. A total of 15 different types of AID were identified, the predominant one was autoimmune thyroiditis (18/66; 27%). In 46% of patients, the AID was diagnosed before, and in 49%, it was diagnosed after the diagnosis of MS. The presence of family history of AID was not associated with the risk of developing AID. Our analysis found no association between the presence of AID and disease activity (new lesions, gadolinium enhancement, mean of annual relapse rate, initiation of a second‐line treatment), either when considering each variable individually or within a composite score. The median Extended Disability Status Scale and Multiple Sclerosis Severity Score was 1.5 (interquartile range [IQR] 3.0) and 1.0 (IQR 3.0), respectively, in the AID group, and 1.5 (IQR 3.0) and 2.0 (IQR 3.0), respectively, in the control group, and the difference was not statistically significant. The presence of a concomitant AID influenced therapeutic choice in nine patients. Conclusions: The present study underlines the varied range of AID that might coexist with MS. This common ground does not seem to have a negative effect on the disease course. Abstract : The common ground for autoimmune diseases and multiple sclerosis disease course.